Immunoassay of infectious agents - Peter E. Andreotti; George V. Ludwig; Anne Harwood Peruski; James J. Tuite; Stephen S. Morse; Leonard F. Peruski (BioTechniques)
Immunoassays have evolved for a broad range of applications since the pioneering work of Yalow and Berson who developed the first competitive radioimmunoassay (RIA) for human insulin in 1959. Immunoassay detection of specific antigens and host-produced antibodies directed against such antigens constitutes one of the most widely used and successful methods for diagnosing infectious diseases (IDs). The number and variety of new assay systems that are continually being developed reflect the increasing demand for immunoassays possessing greater sensitivity, speed, and ease of use. This trend has been driven, in part, by the need for improved immunodiagnostic systems to perform rapid testing and counter emerging IDs and biothreat (BT) agents. Another factor driving this trend is the need to integrate immunoassays with more sensitive nucleic acid-based methods for a comprehensive approach. Here we examine the development of immunoassays, some of the key formats used for the detection and identification of BT/ID agents, and the application of these technologies under different scenarios.